The Effect of Restaurant, Entertainment and Hotel Tax to Sustainability of Local Revenue - BRILLIANT ADIN RIJJAL; Novi Dirgantari (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2024)
The problems with regional financial sustainability in all of South Kalimantan Province's districts and cities are the driving force behind this research. The dependence of regional financial management on the mining sector makes the management of restaurant, entertainment and hotel taxes less than optimal as a source of Regional Original Revenue. The purpose of this study is to examine the effect of restaurant, entertainment and hotel taxes on Regional Original Revenue in all Regencies and Cities in South Kalimantan during 2019 to 2021. The sample used consisted of 13 districts and cities using saturated samples. The findings of the regression test demonstrate that although hotel taxes have positive impact on municipal income, taxes on restaurants and entertainment have no effect. This study's disadvantage is that it only looks at three different kinds of municipal tax variables restaurant, entertainment, and hotel taxes without looking at demographics, location, or income level as moderating or intervening variables. Positive effects from local taxes are possible if they are backed by sufficient geographic and demographic considerations.